Cognitive deficits in schizophrenia: specific patterns, neural correlates and remediation through training$nElektronische Ressource - Rentrop, Mirjam (2012)
Research on cognition in people with schizophrenia has provoked a lot of interest for two reasons: It offers a better understanding of the neurobiological components of the disorder and it helps creating effective treatments for cognitive deficits, which limit the possible functional outcome after remission. The three studies presented here are all concerned with cognitive deficits in schizophrenia, but they focus on different levels, from electrophysiology to work ability in a clinical setting. The first two studies addressed the question of an underlying core deficit of the disorder, which might lead to the clinical features of the illness, in particular the commonly observed broad cognitive impairments. In both studies we hypothesized that increased intra-individual variability could be found in a high-functioning sample of patients with schizophrenia. The first study concentrated on response times whereas the second used an electrophysiological measure. The third study directly compared two cognitive trainings which work on different levels – one working with basic cognitive functions like memory and attention and one specifically training planning and problem solving as a part of higher cognitive functioning. The first study did not only find increased intra-individual variability in high-functioning patients with schizophrenia but could show an association between increased variability of response times and poorer work ability. The second study found that on an electrophysiological level increased temporal variability was found when analysing single trials of the N2 component, and that higher variability was linked with a more widespread activation during the N2 time-window. The third study comparing the two trainings did not find a clear advantage of one over the other. Both trainings lead to some improvements in cognitive functioning and work ability. There was an indication that planning ability improved more when trained directly instead of being trained via basic cognitive abilities. The first two studies emphasize the importance of intra-individual variability for schizophrenia and its occurrence on different levels. The association between response variability and work ability further highlights the importance of this measure. The third study indicates that a new training focussing specifically on planning and problem solving had an effect comparable to that of a more conventional training for patients with schizophrenia. Its results show how important it is to directly compare different kinds of training with each other and with a control group. In conjunction, the three studies provide the basis for further research into putative cognitive and neurophysiological core deficits of schizophrenia, which could provide a theoretical basis for the development of cognitive training programs.
Online publiziert: 2014
Keywords: Hochschulschrift